Buffer time allocation in liner shipping schedule design with sea time and port time uncertainty - Liu, Yuhan (2017)
This study deals with the tactical-level design of buffer time in liner shipping network which aims to determine the optimal buffer time to be added into each voyage leg by taking into account time uncertainties at sea and port. This problem is formulated as a mixed-integer nonlinear stochastic programming model. It first derives the optimal speed on each voyage leg for a closed-loop route under the assumption of zero uncertainty and subsequently incorporates the factor of sea time and port time uncertainties by random variables and introduces buffer time to hedge against uncertainties. The objective of the model is to balance the trade-off between schedule reliability and cost in which intangible costs are quantified by functions. This model is applicable to new shipping routes planning as well as existing shipping routes modification in terms of optimal buffer time amount.